Desain Instalasi Listrik Bangunan Bertingkat (Studi Kasus: Pesantren Khoiru Ummah Sumedang) - Ibnu Hajar; Dhami Johar Damiri; Yuliasyah Yuliasyah; Jumiati Jumiati; M. Syair Pandu Lesmana; Muhammad Iqbal Romadhoni (Terang, 2020)
The electrical installation is a circuit of electrical equipment which is interconnected with one another and it is within the scope of the electrical power system. This article is to present the result of social community service (PkM) activity at Boarding School of STP SMP/SMA KU Sumedang, that shows an electrical installation design of multi-storey building. In construction of multi-storey building of this boarding school, they do not have an electrical installation design. So, the design in this article is to provide design drawings of the electrical installation, so it could be guidance of setting up of electrical installation for the new boarding school building. So that, they got the electrical installation safely for human and the equipment, as well reliable and comfort during using electricity. The design drawings that resulted from the social community service are drawings of front look, beside look, wiring, and single line diagram (SLD). Also, resulted total power calculation, protection, and capacity (rating) of MCB, and calculated cable rating (KHA), choosing type and cross-sectional area of cables that will be used in electrical installation design for the boarding school building.